Matter Production Characteristics and Nitrogen Use Efficiency under Different Nitrogen Application Patterns in Chinese Double-Cropping Rice Systems - Wentao Zhou; Wenfei Long; Hongrui Wang; Pan Long; Ying Xu; Zhiqiang Fu (Agronomy, 2022)
Panicle-stage nitrogen fertilizer is popular in parts of China due to its higher nitrogen recovery efficiency compared to basal and tiller nitrogen. However, the effect of conversion from basal to panicle-stage nitrogen on matter production, grain yield, and nitrogen use efficiencies (NUE) in Chinese double-cropping rice systems remains largely unknown. Here, we elucidate the effect by using two types of one-time basal nitrogen patterns (A and B), three panicle-N allocation patterns (C, D, and E), and the local conventional patterns (CK). The two-year experiment demonstrates that E (basal/tiller/spikelet-promoting /spikelet-developing nitrogen = 0:4:3:3) produced the greatest annual grain yield, nitrogen agronomic efficiency, and nitrogen partial productivity. The annual dry matter weight and nitrogen increment of panicle, nitrogen transportation of stems contributes the most to annual yield and NUE. Furthermore, the yield increase could be attributed to the higher effective panicles, plant dry matter weight at tillering, and net photosynthesis rate at heading. Moreover, years and varieties affect the yield in different N treatments. The improvement in the net photosynthesis rate at the milk stage also significantly increases nitrogen recovery efficiency. These findings suggest that it is worth paying attention to the rational ratio of tillering to panicle fertilizer without applying a base fertilizer, to synchronously increase the grain yield, NUE in Chinese double-cropping rice systems.